Impact of reduced antibiotic treatment duration on antimicrobial resistance in critically ill patients in the randomized controlled SAPS-trial - Shajiei, Arezoo; Berends, Matthijs S.; Luz, Christian F.; van Oers, Jos A.; Harmsen, Hermie J. M.; Vos, Piet; Klont, Rob; Loef, Bert G.; Reidinga, Auke C.; Bormans-Russell, Laura; Linsen, Kitty; Dormans, Tom; et al. (Frontiers in Medicine, 2023)
Background: In the previously reported SAPS trial (https://clinicaltrials.gov/ct2/show/NCT01139489), procalcitonin-guidance safely reduced the duration of antibiotic treatment in critically ill patients. We assessed the impact of shorter antibiotic treatment on antimicrobial resistance development in SAPS patients. Materials and methods: Cultures were assessed for the presence of multi-drug resistant (MDR) or highly resistant organisms (HRMO) and compared between PCT-guided and control patients. Baseline isolates from 30d before to 5d after randomization were compared with those from 5d to 30d post-randomization. The primary endpoint was the incidence of new MDR/HRMO positive patients. Results: In total, 8113 cultures with 96,515 antibiotic test results were evaluated for 439 and 482 patients randomized to the PCT and control groups respectively. Disease severity at admission was similar for both groups. Median (IQR) durations of the first course of antibiotics were 6d (4-10) and 7d (5–11) respectively (p=0.0001). Antibiotic-free days were 7d (IQR 0–14) and 6d (0–13) (p=0.05). Of all isolates assessed, 13% were MDR/HRMO positive and at baseline 186 (20%) patients were MDR/HMRO-positive. The incidence of new MDR/HRMO was 39 (8.9%) and 45 (9.3%) in PCT and control patients respectively (p=0.82).The time courses for MDR/HRMO development were also similar for both groups (p=0.33). Conclusions: In the 921 randomized patients studied, the small but statistically significant reduction in antibiotic treatment in the PCT-group did not translate into a detectable change in antimicrobial resistance. Studies with larger differences in antibiotic treatment duration, larger study populations or populations with higher MDR/HRMO incidences might detect such differences.